Relações entre capital psicológico e motivação : um estudo em organizações de saúde do Rio Grande do Sul - Fidelis, Andréa Cristina Fermiano (My University, 2016)
The Psychological Capital and the theory of self-determination, through the study of motivation for the job are related areas will research of human behavior in organizations. Both approaches propose measuring instruments to check the influence of subjective factors in human performance in companies. Based on these two theoretical approaches, empirical research was carried out quantitative and qualitative in order to check whether there is a relationship between Demotivation, Extrinsic Motivation Intrinsic Motivation and with the dimensions of Psychological Capital (Self-efficacy, hope, optimism and resilience). The study sample consisted of 235 workers in the health sector, in Rio Grande do Sul / BR. In the quantitative stage was used the PCQ -24 instruments and MWMS in active employees of administrative and healthcare area, in hospitals and medical clinics. In the qualitative phase were conducted open interviews with five people who participated in the quantitative sample. The methodological procedures used were factor analysis, ANOVA and Correlation Matrix for quantitative and content analysis approach in the qualitative approach. Among the findings highlight that there is a negative correlation between Psychological Capital and Demotivation well as a positive correlation between the dimensions of Psychological Capital and Motivation Intrinsic. Considering the motivation as a continuum between Motivation Extrinsic and Intrinsic Motivation, it was observed that the higher the level of Psychological Capital in individuals over the results closer to the type of Intrinsic Motivation levels. Statistical results suggest that professionals working in care have higher motivation levels to work and Psychological Capital of the administration area. Similarly people with full grade level showed high levels of motivation and Psychological Capital compared to individuals without complete schooling. In qualitative research it was found that the reflex action triggered by participation in the quantitative stage of the study resulted in four main ideas; and self-reflection on the work, the lack of focus on human, the split between task and people and the motivation for the performance of work activities. These 'key ideas' were discussed by theoretical approaches that have supported this research.
O Capital Psicológico e a teoria da Autodeterminação, através do estudo da Motivação para o trabalho, são áreas relacionadas à pesquisa do comportamento humano nas organizações. Ambas as abordagens propõem instrumentos de medida para verificar a influência de fatores subjetivos no desempenho humano nas empresas. Com base nestas duas abordagens teóricas, foi realizada investigação empírica de natureza quantitativa e qualitativa com o objetivo de verificar se existem relações entre as categorias de Desmotivação, Motivação Extrínseca e Motivação Intrínseca com as dimensões do Capital Psicológico (Autoeficácia, Esperança, Otimismo e Resiliência). A amostra pesquisada foi composta por 235 trabalhadores que atuam no segmento da saúde, no Rio Grande do Sul/BR. Na etapa quantitativa foram utilizados os instrumentos PCQ -24 e o MWMS, respondidos por funcionários ativos da área administrativa e assistencial, em hospitais e clínicas médicas. Na etapa qualitativa foram realizadas entrevistas abertas com cinco pessoas que participaram da amostra quantitativa. Os procedimentos metodológicos utilizados foram Análise Fatorial, ANOVA e Matriz de Correlação para a abordagem quantitativa e Análise de Conteúdo na abordagem qualitativa. Dentre os resultados encontrados, destaca-se que há uma correlação negativa entre o Capital Psicológico e a Desmotivação bem como uma correlação positiva entre as dimensões deste Capital Psicológico e Motivação Intrínseca. Considerando a motivação como um continuum entre Motivação Extrínseca e Motivação Intrínseca, observou-se que quanto maior o nível de Capital Psicológico nos indivíduos mais os resultados aproximavam-se dos níveis de motivação do tipo Intrínseca. Os resultados estatísticos sugerem que os profissionais que atuam na assistência possuem maiores níveis de Motivação para o trabalho e Capital Psicológico do que os da área administrativa. Da mesma forma, pessoas com nível de graduação completa apresentaram níveis elevados de Motivação e Capital Psicológico quando comparados aos indivíduos sem escolaridade concluída. Na pesquisa qualitativa constatou-se que a ação reflexiva desencadeada pela participação na etapa quantitativa deste estudo resultou em quatro ideias principais: a autorreflexão sobre o trabalho, a falta de foco no aspecto humano, a cisão entre tarefa e pessoas e a motivação para o desempenho das atividades laborais. Estas ‘ideias principais’ foram discutidas através das abordagens teóricas que deram suporte a esta pesquisa.
Keywords: Motivação no trabalho; Instituições de saúde - Rio Grande do Sul - Administração; Employee motivation; Health facilities - Rio Grande do Sul (Brazil) - Administration